Coincident Indicators of Capital Flows - Pant, Malika (IMF Working Papers; Working Paper ;, 2012)
Capital flows data from Balance of Payments statistics often lag 3-6 months, which renders timely surveillance and policy deliberation difficult. To address the tension, we propose two coincident composite indicators for capital flows that improve upon existing proxies. We find that the most widely used proxy, the capital tracker, often overpredicts net flows by 30 percent. We augment the tracker into a composite indicator by assigning to it a lesser but optimally estimated weight while incorporating other regional and global coincident correlates of capital flows. The proposed composite indicator of net flows outperforms the capital tracker in its original format. To complement the indicator with an even timelier variant, we also utilize the EPFR high frequency coverage of gross bond and equity flows as an indicator on foreign investors' sentiment.